Las metodologías activas en la discalculia operacional, en estudiantes del quinto grado de la Unidad Educativa Fiscomisional “La Dolorosa”, periodo lectivo 2021-2022 - Jumbo Masache, Micaela Nohemy (2022)
The curricular integration work called: Active methodologies in operational dyscalculia, in fifth grade students of the Unidad Educativa Fiscomisional "La Dolorosa", school year 2021-2022, has as general objective to implement active methodologies that favor the solution of operational dyscalculia, likewise as specific objectives the following were proposed: to diagnose the difficulties presented by fifth grade students in the subject of Mathematics, to design and to implement an educational proposal based on active methodologies, and finally to evaluate the efficiency of active methodologies for the improvement of students learning; this study has the importance of addressing the problem of operational dyscalculia in students through the use of active methodologies that promote motivating, interactive and meaningful learning. This research was developed through a quali-quantitative, exploratory, descriptive and statistical approach, it worked with a scientific, analytical, descriptive and statistical method; the techniques were observation, structured interview, survey and Smartick Method, the instruments were direct observation guide, questionnaire and pre- and post-test: Smartick Method, the sample population is composed of 1 teacher and 16 students; the results obtained in the pre-test: Smartick method based on the grading scale of the MINEDUC, it can be alluded that 94% of the students are closed to reach the required learning, while the other 6% of the students do not reach the acquired learning, therefore, we reject the Ho and accept the Ha, that is to say, the means between the pre- and post-test are significantly different, consequently, we conclude that the educational proposal "Learning together with active methodologies" improves significantly the operational dyscalculia presented by the students of the fifth grade of EGB of the Fiscomisional Educational Unit "La Dolorosa" Key words: Mathematics, active methodology , dyscalculia, Smartick, significant.